Jalan Kito Application For Services, Suggestions And Complaints Of Traffic And Land Transfortation (LLAJ) Geographic Information System-Based Safety Facilities - Eka Sahputra; Robby Egi Purnandi (Penerbit Jurnal Indonesia, 2022)
Bengkulu Province Transportation Agency (Dishub) constituses one of the agencies engaged in public services, especially in the Traffic and Land Transportation (LLAJ) section to provide road safety facilities for the community. There are various kinds of facilities that have been provided at several location points, but the Bengkulu Province Transportation Agency (Dishub) does not immediately receive accurate information, resulting in delays in handling the damaged facilities. Therefore, complaints from the public are needed to find out the direct damage that is at the point of location of road safety facilities. Public complaints usually often occur in the field of public facilities and services which are handled by government agencies. The community's complaints have not been conveyed directly properly but only through social media intermediaries so that it makes people confused about who to complain to. So in this study, we will discuss the Jalan Kito application which is a service for advice and complaints of the Traffic and Land Transportation(LLAJ) safety facilities based on the Geographic Information System to help the public in reporting damage to road safety facilities. This study employed the Extreme Programming, Extreme Programming (XP) method, which is a software development method that is fast, efficient, low risk, flexible, predictable, scientific, and fun. This model tends to use an Object-Oriented approach. The stages that must be passed include Planning, Design, Coding, and Testing, For testing, it used the Black Box method. In testing with this Black Box method, the results obtained are that all menus, pages, and features that are made run according to what is expected